Exogenous application of melatonin to plants, algae, and harvested products to sustain agricultural productivity and enhance nutritional and nutraceutical value: A meta-analysis - Agathokleous, Evgenios; Zhou, Boya; Xu, Jianing; Ioannou, Andreas; Feng, Zhaozhong; Saitanis, Costas J.; Frei, Michael; Calabrese, Edward J.; Fotopoulos, Vasileios (My University, 2021)
Melatonin is produced by plants, algae, and animals. Worldwide studies show diverse positive effects of exogenous melatonin on plants, edible plant products, and algae, but the potential of melatonin to enhance food and feed systems through these positive effects remains largely unexplored. Through a meta-analysis of about 25,000 observations, we show for the first time that exogenous application of melatonin significantly increases crop productivity and yields, and enhances the nutritional and nutraceutical value of edible plant products and algae by regulating diverse biological functions. We demonstrate that melatonin can improve plants, edible plant products, and algae under various current climate change scenarios, environmental pollution factors, and other stresses by about 7% to nearly 30%, on average, depending on the stressor. We also analyze various technical/methodological factors influencing the desired outcomes and identify conditions that offer optimal enhancement. We show that the positive effect of melatonin on plants and edible plant products varies among species, genera, and families, and strongly depends on the concentration of melatonin and treatment duration. The effect of melatonin is slightly lower on the monocot clade Commelinids than on the eudicot clades Asterids and Rosids. We also show that its stimulatory effect on plants depends on cultivation system, with a larger effect obtained in hydroponic systems. However, it does not depend on application stage (seed or vegetative), application route (foliage, roots, or seed), and whether the cultivation system is ex vivo or in vivo. This is the first meta-analysis examining the effects of melatonin on plants, edible plant products, and algae, and offers a scientific and technical roadmap facilitating sustainable food and feed production through the application of exogenous melatonin.
Keywords: Climate change; Edible plants; Environmental pollution; Food security; Fruit; Hunger; Melatonin; Nutritive value; Physiological stress; Sustainable agriculture